388Investigating the utility of the customised fetal growth chart: a pragmatic randomised controlled trial. (2nd September 2021) - Gibbons, Kristen; Beckmann, Michael; Flenady, Vicki; Gardenre, Glenn; Gray, Peter
Abstract: Background: To determine if the routine use of a customised fetal growth chart, when compared to a standard growth chart, reduces the risk of adverse pregnancy outcome through increased detection of adverse growth. Methods: A double-blind, single centre, randomised controlled trial was conducted. All women with a singleton pregnancy receiving routine antenatal care through hospital clinics were included and randomised to either a standard growth chart (SC) or a customised growth chart (CC). Serial measurements of symphyseal fundal height (SFH) were plotted onto the chart in the electronic clinical record; pre-programmed alerts notified the clinician when growth or size required review. The primary outcome measure was a composite perinatal morbidity/mortality outcome. Results: 3993 women were recruited; 45.4% nulliparous; 50.0% Caucasian, 17.8% Asian; 34.9% were overweight/obese prior to pregnancy; average 30 (SD 5.5) years old. The median (IQR) number of growth alerts was 2 (0-3) for both groups (p = 0.378); there was no difference in the total number of ultrasounds per pregnancy (median [IQR] 3 [2-4] for both groups, p = 0.266). There was no significant difference in primary composite outcome (CC 6.4%, SC 7.5%, p = 0.171) or individual components, apart from stillbirth (CC n = 1 0.05%, SC n = 8 0.4%, p = 0.039). Conclusions: Use of a CC resulted in no difference in primary outcome, number of growth alerts or number of ultrasounds. Key messages: In a large, pragmatic RCT use of a CC in conjunction with serial SFH measurements may infer some benefit over a SC, particularly in relation to stillbirth.